Les ghāṭ de Bénarès - Savitri Jalais (Projets de Paysage)
The ghāṭs in Benares closely follow the contours of the steep left bank of the river Ganges. The development of this waterfront in time and the various ways in which each architectural element is integrated with the river bank, calls into question the city’s impressive urban unity. This article explores the ways in which the ghāṭs adapt to a specific river environment and a characteristic topography, so as to protect the river bank from the erosive and devastating action of the river, to preserve the characteristics of its landscape and to accompany the sacred practices linked to the culture of the place. The ability of the spatial device to adapt could explain the urban potential inherent to its development in time and space i.e.along the river bank.